Anxiolytic effects of Chrysanthemum morifolium Ramat Carbonisata-based carbon dots in mCPP-induced anxiety-like behavior in mice: a nature-inspired approach - Cui, Luming; Zhang, Qian; Zhang, Yifan; Li, Tingjie; Li, Menghan; Yuan, Jinye; Wu, Zhiyi; Zhang, Yue; Kong, Hui; Qu, Huihua; Zhao, Yan (Frontiers in Molecular Biosciences, 2023)
Anxiety disorders have emerged as a predominant health concern, yet existing pharmacological treatments for anxiety still present various challenges. Chrysanthemum morifolium Ramat Carbonisata (CMRC) has been utilized in China for approximately 400 years as a therapeutic intervention for anxiety disorders. In this study, a novel type of carbon dots derived from the decoction of Chrysanthemum morifolium Ramat Carbonisata (CMRC-CDs) was identified and isolated, and their morphological structure and functional groups were characterized. Furthermore, the effects of CMRC-CDs on m-chlorophenylpiperazine (mCPP)-induced anxiety-like behaviour in mice were examined and quantified. In order to investigate the potential mechanisms of their anxiolytic effects, concentrations of hypothalamic-pituitaryadrenal (HPA) axis hormones, amino acid neurotransmitters, and monoamine neurotransmitters were measured. CMRC-CDs were spherical and homogeneously dispersed, with diameters ranging from 1.4 to 4.0 nm and an abundance of chemical groups on their surface. In the open-field (OF) test, mice pre-treated with CMRC-CDs demonstrated an increased proportion of time spent in the central area and a higher frequency of entries into the central area. In the elevated plus maze (EPM) test, mice pre-treated with CMRC-CDs exhibited a greater number of entries into open arms and an extended duration spent in open arms. CMRC-CDs were observed to decrease serum concentrations of corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosterone (CORT). Furthermore, CMRC-CDs were found to increase γ-aminobutyric acid (GABA) and 5-hydroxytryptamine (5-HT) levels, while concurrently reducing glutamic acid (Glu) concentrations in brain tissue. CMRC-CDs demonstrated anxiolytic effects, which may be attributed to their modulation of hormones and neurotransmitters. This discovery implicates the potential therapeutic utility of CMRC-CDs for clinical interventions in managing anxiety disorders.